EFFECT OF LAND AREA, PRODUCTION AND RUBBER PRICES ON THE INCOME OF RUBBER FARMERS IN NORTH SUMATERA - Ramadani, Riski; Lubis, Mitra Musika; Ilvira, Rika Fitri (Institute of Computer Science (IOCS), 2024)
The research aims to determine the effect of land area, production and price of rubber on the income of smallholder rubber farmers in North Sumatra Province. This research was conducted in North Sumatra Province. The basis for choosing the location for this study was 10 of 33 districts in North Sumatra. This research was conducted in November-December in 2022. The data used in this study is secondary time series data with a range of 2017-2021 with data sources from the Central Statistics Agency, the Central Statistics Agency for Medan City, North Sumatra. The data used are data on rubber planting area, rubber production, rubber prices and rubber farmer income from 10 districts namely Mandailing Natal, Langkat, North Padang Lawas, South Labuhan Batu, Central Tapanuli, Labuhan Batu, Padang Lawas, Serdang Bedagai, Labuhan Batu North and South Nias. Data analysis was performed using multiple linear regression analysis with the independent variables consisting of rubber planting area (X1), rubber production (X2), rubber prices (X3), while the dependent variable consisted of rubber farmer income (Y). The results showed that partially rubber production and rubber prices had a significant effect on the income of rubber farmers in North Sumatra province, while the area of rubber plantations had no significant effect on the income of rubber farmers in North Sumatra province. Simultaneously the area of rubber plantations, rubber production and rubber prices has a significant effect on the income of rubber farmers in the province of North Sumatra.Keywords: Sweet Potato, Variety, Source of Potassium.